DIAGNOSIS AND FOLLOW-UP OF THE PERIAPICAL LESIONS IN THE NON-SURGICAL ENDODONTIC TREATMENT: A CBCT STUDY - Mihaela Sălceanu; Maria Vataman; Liana Aminov; Cristi Giuroiu; Claudiu Topoliceanu; Yllka Decolli; Cristina-Angela Ghiorghe; Anca Melian (Romanian Society of Oral Rehabilitation, 2017)
Aim of the study The study aimed to determine, by using CBCT, the prevalence and the extension of the periapical healing processes during short term follow-up of the endodontically treated chronic apical lesions. Material and methods Using CBCT examen, 15 teeth (20 roots) affected by chronic apical periodontitis were selected for this study. Ez3D 2009 Plus software was used to perform accurate measurements of bone lesions before and 3 months after treatment. Results The results of our study show the partial healing of the chronic periapical lesions after nonsurgical endodontic treatment, with a prevalence of the healing reactions of 77% for CAP with CBCT-PAI 3, 43% for CAP with CBCT-PAI 4, and 25% for CAP with CBCT-PAI 5. For the entire study group, partial healing was observed at 3 months follow-up in 65% cases, with higher percents (77%) for teeth with CBCT-PAI 3. Conclusion CBCT diagnostic and the follow-up of the results in the case of the non-surgical endodontic therapy of the chronic apical periodontitis is a reliable tool that must be considered for an extended use in the endodontic field.